Women’s career motivation: social barriers and enablers in Sudan - Mohamed, Souad; Abbashar, Aida; Abushama, Hala (Frontiers in Psychology, 2023)
Introduction This study presents an original contribution by examining an often-neglected country in the Middle East and Northeast Africa (MENA), with a specific focus on women’s career research. It identifies challenges that have created barriers for Sudanese women’s career progression, consequently limiting their opportunities for career and leadership growth. To conceptualize understand women’s career motivations on a global and regional scale, the study conducted an in-depth review and analysis of literature, benchmarked similar countries, and incorporated psychological and organizational behavior theories, alongside examples of women’s empowerment cases from the MENA region. Methods The study employs a multifaceted approach that involves exploring psychological and organizational theories, drawing insights from self-efficacy, stereotype, and implicit bias theories, as well as MENA empowerment cases. Additionally, an empirical investigation is conducted through an extensive three-round Delphi study involving 75 Sudanese women leaders from diverse sectors. The empirical findings are crucial for understanding obstacles faced by women and the impact of Sudan’s unique social context on their career paths. Results The research findings shed light on the complex interplay of factors creating roadblocks for Sudanese women’s career advancement. Sudan’s distinctive social context significantly shapes and influences women’s career motivations in diverse and interconnected ways. Empirical evidence from the Delphi study underscores the broad impact of these roadblocks, highlighting the multiplicity of challenges faced by women in Sudan. This comprehensive analysis not only aids in comprehending workplace obstacles but also provides valuable insights into the diverse experiences and needs of female employees. The findings emphasize the broad impact of these barriers on women, underscoring their varied challenges. Discussion The research holds far-reaching implications. By contextually identifying barriers that impede Sudanese women’s career motivations, the study lays a foundation for targeted solutions. This understanding is grounded in historical, theoretical, and policy-making perspectives, enabling informed strategies to support women’s advancement. The study also offers actionable policy recommendations for governments, workplaces, and stakeholders, facilitating women’s career growth through policy reforms and capacity-building initiatives. Furthermore, its significance extends beyond Sudan, acting as a catalyst for developing gender-responsive policies in similar MENA countries and beyond.